Rancang Bangun Aplikasi Pencatatan Keuangan dan Simulasi Investasi Berbasis Web - I Made Rian Suputra; I Made Sukarsa; Anak Agung Ketut Agung Cahyawan Wiranatha (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Accurate financial recording and effective investment management are essential for optimizing the use of financial resources, identifying spending patterns, and maximizing investment growth. The aim of this research is to assist users in managing daily income and expenses, as well as to support decision-making in financial investments. Therefore, it is necessary to develop an application that offers practical solutions for financial recording and investment management. The financial recording and investment simulation application is developed using the Laravel Framework with the waterfall development method. The programming language used is PHP, and the database is MySQL. Application testing was carried out using Black Box Testing to verify functionality and Stress Testing to evaluate system performance and resilience. The Stress Testing scenario involved 100 samples with a ramp-up period of 10 seconds and a loop count of 1, testing one of the API endpoints, namely the news endpoint. The results of the Black Box Testing indicate that the application successfully performs the expected scenarios, and the Stress Testing results show that the application demonstrates adequate resilience under high workload conditions.